Perceived quality of life and acceptance of illness in people with type 2 diabetes mellitus - Rogon, Isabella; Kasprzak, Zbigniew; Szcześniak, Łucja (Menopause Review/Przegląd Menopauzalny, 2017)
Objectives : Type 2 diabetes exerts a significant impact on the patient’s quality of life. Its chronic nature, incurability and complications weaken the motivation of patients to fight the disease and its acceptance. The aim of research was to determine whether and to what extent diabetes modulates the quality of life of patients and in particular which domain of the patient’s life is most limited. In addition, we looked at whether the quality of life perceived by patients is determined by gender and whether and to what extent they accept their illness. Material and methods: A study on 100 patients with type 2 diabetes from the Wielkopolska region in Poland was carried out at the end of 2013/beginning of 2014 using a diagnostic survey, and the research techniques were a standardized questionnaire – ADDQoL19 (Audit of Diabetes-Dependent Quality of Life 19) and the AIS questionnaire (Acceptance of Illness Scale) developed by Felton and modified by Juczyński. Results: The results suggest that the quality of life of the patients was "neither good nor bad", whereby women perceive it as being lower than men. While analysing the impact of diabetes on the different domains of the lives of men and women, it should be stressed that most affected were diet, satisfying appetite, independence, financial position, feelings about the future, sex life, and freedom in the consumption of drinks. More than half of men and women did not accept their illness; however, younger persons unlike older accepted diabetes to a much greater degree. Conclusions : Type 2 diabetes negatively affects the quality of life of patients and its impact is felt more by women. In both sexes, the most affected domain of quality of life is the lack of nutritional freedom. The acceptance of illness is dependent upon age.